Da colaboração confortável para colaboração crítica com um grupo de trabalho constituído por professores de inglês - Gatto, Margareth Guidara (2014)
This paper aims at critically analyzing the senses of collaboration which are spread in a work group that is composed by English teachers, as well as critically analyzing actions that contribute to the construction of critical collaboration in this group. A formative intervention research was carried out in such a way that, according to Engeström (2011), the construction and change of concepts involve confrontation, questioning and negotiation. This work s theoretical framework is founded on the Social-Historical-Cultural Activity Theory, as discussed by Vygotsky (1930/2008; 1934/2001), Leontiev (1977) and Engeström (1987; 1999; 2001/2005); on the concepts of collaboration and reflection discussed by Magalhães (2003/2007; 2007; 2009; 2010); and, on the discussions about argumentation in school contexts proposed by Liberali (2004a) and Leitão & Damianovic (2011). A questionnaire about collaboration was applied to the participants, who received and answered it by email. Reflexive Sessions among participants, held after class observation, were audio-recorded and transcribed. The data were analyzed according to categories that were developed by Liberali (2013), Magalhães (2004), Orsolini (2005), Pontecorvo (2005), Brookfield and Preskill (2005), Magalhães e Fidalgo (2007), concerning the language used by the subjects throughout the intervention. The analysis of the data shows that the sense of collaboration spread in the group of English teachers at the school where the research was done, was the sense of comfortable collaboration. The results also reveal that the actions taken by the teacher-researcher and other participants started to awaken the sense of critical collaboration in the group